Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Une si grande différence - Gilligan, Carol (Flammarion, 1986)
Cela fait des siècles que nous écoutons les voix des hommes et les théories que leur dicte leur expérience. Plus récemment, nous avons commencé, non seulement à remarquer le silence des femmes, mais aussi, la difficulté d'entendre ce qu'elles disent quand elles prennent la parole. " A partir de trois enquêtes psychologiques, Carol Gilligan montre bien que la grande différence entre le masculin et le féminin est une différence de formation et de comportement moral conduisant à deux types psychologiques bien distincts, les femmes se caractérisant par une éthique de sollicitude qui influence leur rapport avec autrui et leur sens des responsabilités. Best-seller aux U.S.A., Une si grande différence est un ouvrage capital du post-féminisme.
Keywords: 1900-1999; amériques; care; cours; différence des sexes; discipline; fem1000; postféminisme; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis; éthique